FASN-Mediated Lipid Metabolism Regulates Goose Granulosa Cells Apoptosis and Steroidogenesis - Chen, Xi; Huang, Kailiang; Hu, Shenqiang; Lan, Gang; Gan, Xiang; Gao, Shanyan; Deng, Yan; Hu, Jiwei; Li, Liang; Hu, Bo; He, Hua; Liu, Hehe; et al. (Frontiers in Physiology, 2020)
Lipid metabolism participates in regulating the functions of granulosa cells, which is important for follicular development. In this experiment, goose granulosa cells from pre-hierarchical follicles and hierarchical follicles were selected to be the model for studying the putative regulatory role of lipid metabolism in apoptosis and steroidogenesis, through overexpression and interference with FASN. When FASN was overexpressed, the lipid accumulation was increased in hierarchical granulosa cells and it was increased in the two categorized granulosa cells when FASN was interfered. In addition, the apoptosis of the two categorized granulosa cells were both increased when FASN was overexpressed, and the progesterone production of them were both decreased when FASN was interfered. The results of qRT-PCR showed that, when FASN was overexpressed, the expression level of CYP11A1 was decreased in pre-hierarchical granulosa cells, while the expression levels of SCD1, DGAT2, APOB and StAR were increased in hierarchical granulosa cells. When FASN was interfered, the expression levels of CPT-1, DGAT2 and StAR were decreased whereas the expression level of CYP11A1 was increased in pre-hierarchical granulosa cells, and the expression levels of CPT-1, SCD1 and StAR were decreased in hierarchical granulosa cells. These results not only identify the different effects of manipulated FASN expression on lipid metabolism of goose pre-hierarchical and hierarchical granulosa cells, but also demonstrate that FASN-mediated lipid metabolism plays an important role in regulating apoptosis and steroidogenesis of in vitro cultured goose granulosa cells.